DRY MATTER AND NUTRIENT ACCUMULATION CURVE IN CABBAGE CROP - Duarte, Luiz Otavio [UNESP]; Clemente, Junta Maria; Borges Caixeta, Ilidio Augusto; Senoski, Marcelo de Paula; Aquino, Leonardo Angelo de (Univ Fed Rural Semi-arido-ufersa, 2019)
Cabbage cultivars currently cultivated present high yield potential and may present differences regarding absorption and use of nutrients. Thus, studies quantifying plant growth and nutrient accumulation are the basis to improve fertilization efficiency and optimize yield. This study aimed to determine the dry matter and nutrient (N, P, K, Ca, Mg, S, Cu, Fe, Mn, and Zn) accumulation curve of cabbage cultivars during two growing seasons. Cultivars Astrus Plus and Green Valley were cultivated during summer-autumn crop season, while Astrus Plus and Fenix during the autumn-winter crop season. Plants were sampled after transplanting at 10-day intervals until harvest. Dry matter and nutrient accumulations are variable with growing season and cultivar. The highest dry matter and nutrient accumulation rates occur in the last ten days of the cycle. Fertilizations with N, P, K, Fe, and Zn should receive more attention due to higher harvest indices.
Keywords: Brassica oleracea var; capitata; Nutrient extraction; Harvest index